Indian Buddhism : a survey with bibliographical notes - Nakamura, Hajime (Delhi : Motilal Banarsidass, 1987)
This work presents a survey of Indian Buddhism with detailed bibliographical notes. Besing itself on recent studies, it is intended to introduce studies in various aspects of Indian Buddhism carried on by Japanese scholars as well as Western and Asian, especially Indian, scholars. The main text constitutes a gengeral survey of the development of Indian Buddhism and studies by scholars past and present are mentioned in full detail in copious footnotes with due evaluations. This work can be regarded, so to speak, as a development with revisions, of the Buddhist portion of M. Winternitz' History of Indian Literature. Major studies before and after Winternitz' work are exhaustively mentioned. As a reference work also this book is of extreme help to scholars and students alike. The work has been edited by Prof. Ramesh Mathur. Contents: Foreword, Preface, I. General Survey of Buddhism, II. early Buddhism: 1. The Time of the Rise of Buddhism, 2. The Life of Gotama Buddha and his Disciples, The Scriptures of Early Buddhism, Aspects of Original Buddhism, The Thought of Early Buddhism, The Practice of Early Buddhism, The Worship of Buddhas and Faith, Social Thought, III. Conservative Buddhism and Transition to Mahayana: Historical background, Philosophical Schools, Philosophical Thought, Biographies of the Buddha, The Poet Asvaghosa and his school, The Avadana Literature, IV. Mahayana Buddhism: Historical Background, Mahayana Sutras, The Philosophical Schools of Mahayana, V. Logicians: Before Dignaga, Dignaga, Dharmakirti, Logicians at the Final Stage, Some Features of Indian Logic, VI. Esoteric Buddhism: the Beginning, Systematization, The Final Stage, Some Features of Esoteric Buddhism, Addenda et Corrigenda, Abbreviations and Periodicals, Index.
Includes bibliographical references and index.
Keywords: Buddhism -- History -- India; Buddhism -- Bibliography -- India